2011
DOI: 10.1155/2011/387570
|View full text |Cite
|
Sign up to set email alerts
|

Primary Extranodal, Extralymphatic Hodgkin Lymphoma of the Mandible

Abstract: Primary extranodal, extralymphatic Hodgkin lymphomas (PEEHLs) are a rare occurrence. When they are encountered, they become diagnostic challenges. We are describing the uniqueness of a case of PEEHL affecting the mandible with his early response to the available chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
0
5
0
3
Order By: Relevance
“…Lymphomas are malignant tumours developed from cells of the lymphatic system and can therefore affect any organ containing lymphoid tissue. While Hodgkin lymphomas (HL) most often involve lymph nodes in the head and neck, non-Hodgkin lymphomas (NHL) can equally affect extra-nodal sites [ 41 ] such as the lacrimal glands, salivary glands, muscles and soft tissues of the orbit, thyroid gland, maxilla and mandible. Mandibular NHL is very rare.…”
Section: Pitfallsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphomas are malignant tumours developed from cells of the lymphatic system and can therefore affect any organ containing lymphoid tissue. While Hodgkin lymphomas (HL) most often involve lymph nodes in the head and neck, non-Hodgkin lymphomas (NHL) can equally affect extra-nodal sites [ 41 ] such as the lacrimal glands, salivary glands, muscles and soft tissues of the orbit, thyroid gland, maxilla and mandible. Mandibular NHL is very rare.…”
Section: Pitfallsmentioning
confidence: 99%
“…18 ). Radiological findings can be quite subtle such as teeth displacement in the occlusal direction and loss of the lamina dura with widening of the periodontal ligament space [ 41 ]. Rarely, mandibular NHL can present with minor osteolysis or with unilateral enlargement of the mandibular canal and mental foramen (Fig.…”
Section: Pitfallsmentioning
confidence: 99%
“…Some of the cases have been associated with extra-osseous involvement. Primary osseous HL confined to the bone is so rare that approximately 19 cases have been reported worldwide to date, only 12 patients with primary solitary osseous HL [ 7 - 14 ] and 7 patients with primary multifocal osseous HL disease have been reported without lymphatic manifestations [ 15 - 20 ]. Moreover, primary osseous HL presenting as a bone lesion with an associated soft tissue mass is quite unusual [ 10 , 21 - 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…Primary osseous HL that is limited to the bone is extremely rare, and until 2009, only 16 cases had been identified globally ( 10 ). To the best of our knowledge, ~20 cases of primary osseous HL, including 13 patients with primary solitary osseous HL and seven patients with primary multifocal osseous HL without lymphatic manifestations, have been reported ( 11 17 ). Li et al ( 18 ) reported ~30 HL patients with extraosseous involvement.…”
Section: Discussionmentioning
confidence: 99%